Action of kangaroo position for pain relief in newborn preterm submitted to venous punctuation (Research, Society and Development, 2020)
Objective: to verify the action of the kangaroo position for pain relief in preterm newborns submitted to venipuncture. Metodology: an observational, descriptive, control case study of preterm infants who used and did not use kangaroo positioning during venipuncture. For neonates' evaluation of pain, the Neonatal Infant Pain Scale was used with application immediately after the examination and 20 minutes later. Thirty-one preterm infants were evaluated, 16 of whom were in the kangaroo position and 16 in the control group without the kangaroo position. Results: Preterm newborns who were not in the kangaroo position had pain concentration at the strong level (93.8%), while 43.8% of the preterm infants who were in the kangaroo position did not present pain symptoms. It was observed that there was a significant result regarding pain relief (p